2023
DOI: 10.1093/hr/uhad002
|View full text |Cite
|
Sign up to set email alerts
|

High-quality haplotype-resolved genome assembly of cultivated octoploid strawberry

Abstract: Cultivated strawberry (Fragaria × ananassa), a perennial herb belonging to the family Rosaceae, is a complex octoploid with high heterozygosity at most loci. However, there is no research on the haplotype of the octoploid strawberry genome. Here we aimed to obtain a high-quality genome of the cultivated strawberry cultivar, ‘Yanli’, using single molecule real-time sequencing and high-throughput chromosome conformation capture technology. The ‘Yanli’ genome was 823 Mb in size, with a long terminal repeat assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…The recent availability of high‐quality reference genomes and sequence datasets for strawberry has provided essential resources for trait mapping, functional genomics, and genetic marker development in this allo‐octoploid hybrid species (Bassil et al., 2015; Edger et al., 2019; Hardigan et al., 2020, 2021; Lee et al., 2021; Hardigan et al., 2021; Mao et al., 2023; Shirasawa et al., 2021). The growing molecular breeding toolbox for strawberry has nevertheless needed cost‐effective high‐throughput marker genotyping solutions to enable genomic selection and routine forensic identification of individuals and parents on a large scale (Gezan et al., 2017; Jiménez et al., 2023; Osorio et al., 2021; Pincot et al., 2020, 2021; Whitaker et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent availability of high‐quality reference genomes and sequence datasets for strawberry has provided essential resources for trait mapping, functional genomics, and genetic marker development in this allo‐octoploid hybrid species (Bassil et al., 2015; Edger et al., 2019; Hardigan et al., 2020, 2021; Lee et al., 2021; Hardigan et al., 2021; Mao et al., 2023; Shirasawa et al., 2021). The growing molecular breeding toolbox for strawberry has nevertheless needed cost‐effective high‐throughput marker genotyping solutions to enable genomic selection and routine forensic identification of individuals and parents on a large scale (Gezan et al., 2017; Jiménez et al., 2023; Osorio et al., 2021; Pincot et al., 2020, 2021; Whitaker et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The publication of multiple single nucleotide polymorphism (SNP) arrays for strawberry from 2015 to 2020 enabled genetic and physical mapping of new loci controlling traits related to disease resistance and fruit quality (Bassil et al., 2015; Barbey et al., 2021; Castillejo et al., 2020; Jiménez et al., 2023; Noh et al., 2018; Nelson et al., 2021; Nellist et al., 2019; Oh et al., 2019; Osorio et al., 2021; Oh et al., 2021; Pincot et al., 2018, 2020, 2021, 2022; Pillet et al., 2017; Petrasch et al., 2022; Salinas et al., 2019). Progress in this area has only increased following the publication of multiple high‐quality, chromosome‐scale assemblies of octoploid Fragaria genomes in the last 5 years (Edger et al., 2019; Hardigan et al., 2021; Lee et al., 2021; Mao et al., 2023; Shirasawa et al., 2021). These genome assemblies, in combination with resequencing, genomic variant calling, and linkage mapping have demonstrated that strawberry contains mainly diploid‐behaving subgenomes with sufficient sequence divergence, in many cases, to allow targeting of specific homeologous sites for marker genotyping and, potentially, future CRISPR editing (Hardigan et al., 2020, 2021; Ledda et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was extracted from different-stage fruits using the CTAB method (Lei et al 2020). The library for RNA sequencing was constructed as described by Mao et al 2023. The RNA-seq data were uploaded to NCBI and the accession number is PRJNA975298.…”
Section: Rna Isolation and Transcriptome Sequencingmentioning
confidence: 99%
“…In addition, Lin et al (2021) also found some key regulators with anthocyanin synthesis in strawberries through transcriptome sequencing without the reference genome. Recently, our team assembled a haplotype-resolved genome of cultivated octoploid strawberries (Mao et al 2023). This study identi ed crucial genes involved in anthocyanin synthesis in cultivated strawberries based on the transcriptome data and the haplotyperesolved genome of cultivated octoploid strawberries.…”
Section: Introductionmentioning
confidence: 99%
“…Genome sequence further enabled the design of a single nucleotide polymorphism (SNP) 50K array with selected chromosome-specific SNPs 21 allowing the high-resolution mapping of QTLs. A recent breakthrough has been the completion of haplotype-resolved genomes for five genotypes of F. × ananassa 9,22,23,24,25 . These developments make it possible to exploit strawberry diversity through genome wide association studies (GWAS), which scans the genome for significant associations between genetic markers and the trait studied 2 .…”
Section: Introductionmentioning
confidence: 99%